Cholinergic neurons in the dorsomedial hypothalamus regulate mouse brown adipose tissue metabolism - Jae Hoon Jeong; Dong Kun Lee; Clemence Blouet; Henry H. Ruiz; Christoph Buettner; Streamson Chua, Jr; Gary J. Schwartz; Young-Hwan Jo (Elsevier, 2015)
Objective: Brown adipose tissue (BAT) thermogenesis is critical in maintaining body temperature. The dorsomedial hypothalamus (DMH) integrates cutaneous thermosensory signals and regulates adaptive thermogenesis. Here, we study the function and synaptic connectivity of input from DMH cholinergic neurons to sympathetic premotor neurons in the raphe pallidus (Rpa). Methods: In order to selectively manipulate DMH cholinergic neuron activity, we generated transgenic mice expressing channelrhodopsin fused to yellow fluorescent protein (YFP) in cholinergic neurons (choline acetyltransferase (ChAT)-Cre::ChR2-YFP) with the Cre-LoxP technique. In addition, we used an adeno-associated virus carrying the Cre recombinase gene to delete the floxed Chat gene in the DMH. Physiological studies in response to optogenetic stimulation of DMH cholinergic neurons were combined with gene expression and immunocytochemical analyses. Results: A subset of DMH neurons are ChAT-immunopositive neurons. The activity of these neurons is elevated by warm ambient temperature. A phenotype-specific neuronal tracing shows that DMH cholinergic neurons directly project to serotonergic neurons in the Rpa. Optical stimulation of DMH cholinergic neurons decreases BAT activity, which is associated with reduced body core temperature. Furthermore, elevated DMH cholinergic neuron activity decreases the expression of BAT uncoupling protein 1 (Ucp1) and peroxisome proliferator-activated receptor γ coactivator 1 α (Pgc1α) mRNAs, markers of BAT activity. Injection of M2-selective muscarinic receptor antagonists into the 4th ventricle abolishes the effect of optical stimulation. Single cell qRT-PCR analysis of retrogradely identified BAT-projecting neurons in the Rpa shows that all M2 receptor-expressing neurons contain tryptophan hydroxylase 2. In animals lacking the Chat gene in the DMH, exposure to warm temperature reduces neither BAT Ucp1 nor Pgc1α mRNA expression. Conclusion: DMH cholinergic neurons directly send efferent signals to sympathetic premotor neurons in the Rpa. Elevated cholinergic input to this area reduces BAT activity through activation of M2 mAChRs on serotonergic neurons. Therefore, the direct DMHACh-Rpa5-HT pathway may mediate physiological heat-defense responses to elevated environmental temperature.